2018
DOI: 10.1007/s00192-018-3684-5
|View full text |Cite
|
Sign up to set email alerts
|

The symptom of vaginal bulging in nulliparous women aged 25–64 years: a national cohort study

Abstract: The high prevalence of sPOP in this study was contradictory to most earlier reports, which have shown that genital prolapse is rare in nullipara. The explanation of our results may be the low probability of the clinical condition, the dominance of weak and infrequent symptoms, and not least clustering of alternative conditions mimicking sPOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Although it is common knowledge among gynecologists that the relationship between the anatomical stage of POP and sPOP is unpredictable, it has been shown that symptoms increase markedly once the leading edge reaches 1 cm proximal to the introitus, including most patients with POPQ-stage ≥ 2 [ 27 ]. In 199 women with POPQ-stage 0 (parity not specified), Tegerstedt et al found that the “bulging” symptom was reported to occur “infrequently” in 6.0%, “sometimes” in 2.5%, and “often” in 0%, very similar to our results in almost 10,000 nulliparous women aged 25–64 years of age [ 16 , 18 , 21 ]. For women with POP-Q stage < 2, every third reported symptoms of “bulging,” of which 7% had POPQ-stage 0, i.e., were false positive [ 18 ].…”
Section: Strengths and Weaknessessupporting
confidence: 89%
See 1 more Smart Citation
“…Although it is common knowledge among gynecologists that the relationship between the anatomical stage of POP and sPOP is unpredictable, it has been shown that symptoms increase markedly once the leading edge reaches 1 cm proximal to the introitus, including most patients with POPQ-stage ≥ 2 [ 27 ]. In 199 women with POPQ-stage 0 (parity not specified), Tegerstedt et al found that the “bulging” symptom was reported to occur “infrequently” in 6.0%, “sometimes” in 2.5%, and “often” in 0%, very similar to our results in almost 10,000 nulliparous women aged 25–64 years of age [ 16 , 18 , 21 ]. For women with POP-Q stage < 2, every third reported symptoms of “bulging,” of which 7% had POPQ-stage 0, i.e., were false positive [ 18 ].…”
Section: Strengths and Weaknessessupporting
confidence: 89%
“…This study is the fourth report of the Swedish Pregnancy Obesity and Pelvic Floor project in nulliparous women. Earlier studies addressed the age-dependent prevalence of UI, sPOP, and overactive bladder [ 14 16 ]. The questionnaire included questions about current height and weight, childhood NE, urinary incontinence (UI) or fecal incontinence (FI), genital prolapse, nocturia, urgency, and menstrual status (information about current pregnancy, hysterectomy, menopausal status, and hormone treatment).…”
Section: Methodsmentioning
confidence: 99%
“…LISA data can be used to compare responders and non-responders in questionnaire studies. In one study, postal questionnaire non-responders had lower education, lower income, and were more likely to have been born outside Sweden than responders [ 59 , 60 ]. Education and income can be used both as exposures and outcomes, but are most often used as covariates in statistical models [ 61 , 62 ].…”
Section: Contents Of Lisamentioning
confidence: 99%
“…Противоречит указанной концепции также и то, что, несмотря на огромное число научных данных, достоверные морфологические маркеры синдрома так и не найдены, исследования, посвященные их поиску, достаточно спорны [41]. Но теория системной дисплазии соединительной ткани может объяснять раннее развитие пролапса у девочек, подростков и молодых нерожавших женщин [42].…”
Section: гинекологияunclassified